Assessment of the effectiveness of golimumab 50-mg and 100-mg regimens in patients with rheumatoid arthritis in daily practice. Issue 4 (July 2015) - Sato, Eri; Tanaka, Eiichi; Nakajima, Ayako; Inoue, Eisuke; Shimizu, Yoko; Yamaguchi, Rei; Ochiai, Moeko; Shidara, Kumi; Hoshi, Daisuke; Sugimoto, Naoki; Seto, Yohei; Taniguchi, Atsuo; et al.
Abstract Objectives. To assess the effectiveness of the golimumab (GLM) 50-mg and 100-mg regimens in patients with rheumatoid arthritis (RA) in daily practice. Methods. We retrospectively analyzed RA patients who started GLM between September 2011 and July 2012. Patients were divided into three groups: a 50-mg group; a 50/100-mg group (had a dose increase to 100 mg); and a 100-mg group (started GLM at 100 mg). We assessed Disease Activity Score 28 (DAS28) and treatment continuation rate. Risk factors associated with time to discontinuation of the 50-mg regimen were determined with proportional hazards analysis. Results. We analyzed 74 patients: 43 in the 50-mg group, 23 in the 50/100-mg group, and 8 in the 100-mg group. DAS28 improved from 4.0 ± 1.0, 4.8 ± 1.0, and 4.7 ± 1.9, respectively, at baseline to 2.4 ± 1.2, 3.3 ± 1.5, and 2.5 ± 0.7, respectively, at week 52. Treatment continuation rates at week 52 were 73.7%, 60.9%, and 87.5%, respectively. In the 50/100-mg group, the mean DAS28 improved significantly from 4.4 ± 1.2 before to 3.6 ± 1.3 12 weeks after the dose increase. Oral corticosteroid therapy ≥ 5 mg/day, previous use of two biologic agents, and DAS28 > 5.1 at initiation of GLM were significantly associated with discontinuation of the 50-mg regimen. Conclusions. Both GLM 50-mg and 100-mg regimens are effective in patients with RA in daily practice.